Biologic therapy-Related demyelinating peripheral neuropathy in a child with Juvenile Idiopathic Arthritis - Alqurashi, Heba A; Al-Salmi, Ghada; Al-Muhaizea, Mohammad A; Al-Mayouf, Sulaiman M (Archives of Pharmacy and Pharmaceutical Sciences, 2018)
Demyelinating peripheral neuropathy has been described in association with tumor necrosis factor (TNF) inhibitors. It is rarely developed after treatment discontinuation. We present the case of a child with juvenile idiopathic arthritis who developed peripheral neuropathy few months after TNF inhibitor withdrawal with clinical worsening of the neurological sequelae while undergoing treatment with abatacept.